Предмет: Математика, автор: seregenkoilya2008

2(2/3х-1/6)+5 1/3=-4(7/12х+1 3/4)+3(1/9-1/3х) помогите пж

Ответы

Автор ответа: vitalina10222009
3

Ответ:

1 1/3х-1/3+5 1/3=-2 1/3х-7+1/3-х

1 1/3х+5=-3 1/3х- 6 2/3

1 1/3х+3 1/3х=-5-6 2/3

4 2/3х=-11 2/3

х=-11 2/3:4 2/3

х=-2 1/2

Пошаговое объяснение:

Там всё показоно

Автор ответа: accinternet
1

Ответ:

2(2/3x-1/6)+5 1/3= -4(7/12x+1 3/4)+3(1/9-1/3x)= -2 1/2

Пошаговое объяснение:

2(2/3x-1/6)+5 1/3= -4(7/12x+1 3/4)+3(1/9-1/3x)

1 1/3x-1/3+5 1/3= -2 1/3x-7+1/3-1x

1 1/3x+2 1/3x+1x= -7+1/3+1/3-5 1/3

4 2/3x= -11 2/3

x= -2 1/2

Похожие вопросы
Предмет: Русский язык, автор: аааааа24